The Effect of ESG Performance on Firm Value and Financial Distress with ESG Controversies as A Moderating Variable - Daniel Godwin Sihotang; Sylvia Veronica Siregar (Petra International Journal of Business Studies, 2025)
This study aims to analyze the impact of Environmental, Social, and Governance (ESG) performance on firm value and financial distress among non-financial companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2024, with ESG Controversies serving as a moderating variable. Firm value is measured using Tobin’s Q, while financial distress is assessed through the Altman Z-Score. The research dataset consists of 276 company-year observations obtained from Thomson Reuters (Refinitiv) and annual financial reports. Regression results indicate that ESG performance does not have a statistically significant effect on either firm value or financial distress. However, ESG Controversies are found to significantly moderate the relationship between ESG performance and firm value. The interaction between ESG Score and ESG Controversies suggests that ESG-related Controversies weaken the positive effects of strong ESG performance, thereby reducing the potential benefits for firms. On the other hand, this interaction does not show a significant influence on financial distress. These findings suggest that while ESG performance alone has not yet directly influenced financial outcomes, the presence of ESG Controversies can diminish the positive perception of ESG performance and affect market valuation. This study contributes to the existing ESG literature, particularly in emerging markets like Indonesia, by highlighting that beyond ESG scores, reputational factors such as ESG Controversies must also be effectively managed. Practically, this implies that companies should proactively avoid controversial ESG issues to maintain stakeholder trust and enhance long-term sustainability.